2006
DOI: 10.1155/mi/2006/19307
|View full text |Cite
|
Sign up to set email alerts
|

Application of Intracellular Alkaline Phosphatase Activity Measurement in Detection of Neutrophil Adherence In Vitro

Abstract: We have proposed the use of the fluorimetric method with 4-methylumbelliferyl phosphate (4-MUP) specific substrate for the alkaline phosphatase determination in the neutrophil adhesion assay. We provide evidence that the endogenous neutrophil alkaline phosphatase (NAP) activity evaluation is reliable to quantify neutrophil adhesion at a wide range of cell numbers (104−106). The results obtained by fluorimetric NAP activity test correlate to the results of adherence evaluated using the MTT reduction assay. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…The latter molecule is then further hydrolyzed to adenosine by other enzymes, e.g., ecto-5′-nucleotidase and alkaline phosphatase, but none of these two enzymes is present at the cell surface of resting neutrophils [13]. Alkaline phosphatase, however, is present in neutrophil granules and can be secreted as a result of neutrophil degranulation due to fMLP stimulation to subsequently generate adenosine for A 3 activation [13,19]. We know that IL-8 does not induce neutrophil degranulation unless these cells have been pre-treated with cytochalasin B to disrupt the motility response.…”
Section: Discussionmentioning
confidence: 99%
“…The latter molecule is then further hydrolyzed to adenosine by other enzymes, e.g., ecto-5′-nucleotidase and alkaline phosphatase, but none of these two enzymes is present at the cell surface of resting neutrophils [13]. Alkaline phosphatase, however, is present in neutrophil granules and can be secreted as a result of neutrophil degranulation due to fMLP stimulation to subsequently generate adenosine for A 3 activation [13,19]. We know that IL-8 does not induce neutrophil degranulation unless these cells have been pre-treated with cytochalasin B to disrupt the motility response.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil adherence to a plastic surface was detected by measuring the intracellular alkaline phosphatase activity of adherent cells using fl uorogenic substrate 4-methylumbelliferyl phosphate (4-MUP) [23]. Neutrophils untreated or pre-treated with 100 µM of MB, as described, were distributed into 24-well fl at bottom plate (Nunc, Denmark), (1 × 10 5 cells/well), and 10 % of FBS was added to each well.…”
Section: Measurement Of Neutrophil Adhesionmentioning
confidence: 99%
“…This suggests that ALP is closely related to the regression of inflammation. The activity of NAP detected by utilization of the substrate 4-MUP was associated by neutrophil adherence determination in vitro [6]. Zhang et al [21] showed that the expression levels of mNAP in patients with bacteria1 infections were significantly higher than those of patients with virus infections and the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, what NAP acts in the biological function of the human body has not yet been clear. Utilization of the substrate 4-MUP has been recommended as a sensitive, repeatable and reliable method of neutrophil adherence determination in vitro by Bednarska et al [6]. Other studies reported that NAP localized in the secretory vesicles and organelles of neutrophils could be detected after being translocated onto the plasma membrane by f-MLP stimulation [7][8][9].…”
Section: Introductionmentioning
confidence: 99%